CARDIOVASCULAR DISEASES AND THEIR PREVENTION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article scientifically analyzes cardiovascular diseases (CVDs) and their prevention methods. CVDs are the leading cause of death worldwide, threatening the lives of millions each year. The article details the major factors contributing to the development of CVDs, including genetic predisposition, poor diet, physical inactivity, smoking, stress, and other risk factors. The importance of preventive measures, such as adopting a healthy lifestyle, maintaining a balanced diet, engaging in regular physical activity, and undergoing medical check-ups, is examined based on scientific reearch. The article provides evidence that early detection and the application of preventive strategies can significantly reduce the risk of cardiovascular diseases. This study offers scientific recommendations aimed at preserving cardiovascular health and improving overall quality of life.